Business Development. Rural Associative Enterprises on the Path to Self-sufficiency - Sáenz M., Anier; López, Jenny; Centeno Zamora, Janira Damarys; Ordoñez, José Ángel; Ilabaca Ugarte, Carlos (Catholic Relief Services, 2012)
This publication is the result of a participatory experience capitalization, facilitated by the International Center for Tropical Agriculture for the project “Alliance to Create Opportunities for Rural Development through Agro-enterprise Relationships” (ACORDAR). This report addresses the process of transition toward self-sufficiency 23 of the 34 rural business and/or agri-business organizations attended by consortium members and located in 20 municipalities of Nicaragua. Additionally, the report compiles critical reflections on organizational capacity building and strengthening as a strategy to achieve self-sufficiency in rural organizations, from the analytical viewpoint of the ACORDAR team that led the transition process of target organizations.